تكوين البيئة اللغوية في معهد سونان أمبيل العالي على ضوء نظريّة تعلم اللغة العربية السلوكية - Asshiddiqi, Akhmad Irsyad (Maharaat Lughawiyyat: Jurnal Pendidikan Bahasa Arab, 2022)
From there, there are research objectives as follows: 1) To describe the process of forming the language environment in Mahad Sunan Ampel Al-Aly in terms of Behavioristic Learning Theory. 2) Describe the driving factors for the establishment of the language environment at Mahad Sunan Ampel Al-Aly in terms of Behavioristic Learning Theory. 3) Describe the inhibiting factors for the formation of the language environment in Mahad Sunan Ampel Al-aly in terms of Behavioristic Learning Theory. In this study, the researcher used a qualitative method and the type was descriptive. There are three data collection instruments used, namely: interviews, observation, and documentation. The research results are as follows: 1) The process of forming the language environment at Mahad Sunan Ampel Al-Aly in terms of behavioristic learning theory consists of memorizing vocabulary and compiling it into sentences, getting used to using language in daily activities when communicating with musyrif or murobbi. 2) The driving factors for the formation of the language environment at Mahad Sunan Ampel Al-Aly in terms of behavioristic learning theory consist of Mahad Sunan Ampel Al-Aly's desire to form a linguistic culture for students, and the campus's desire that students who have participated in Arabic learning in class with lecturers can be a place for practice from the material 3) The inhibiting factors for the formation of the language environment at Mahad Sunan Ampel Al-Aly in terms of behavioristic learning theory are that environmental conditions are still not supportive, students' activities are still mostly carried out outside the Mahad.